2015
DOI: 10.1016/j.neurobiolaging.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alters resting-state functional connectivity of motor circuits in parkinsonian rats

Abstract: Few studies have examined changes in functional connectivity after long-term aerobic exercise. We examined the effects of 4 weeks of forced running wheel exercise on the resting-state functional connectivity (rsFC) of motor circuits of rats subjected to bilateral 6-hydroxydopamine lesion of the dorsal striatum. Our results showed substantial similarity between lesion-induced changes in rsFC in the rats and alterations in rsFC reported in Parkinson’s disease subjects, including disconnection of the dorsolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 68 publications
(89 reference statements)
0
25
0
Order By: Relevance
“…A recent PET study showed that long-term treadmill exercise partly restores the level of dopamine D2 receptor binding in the striatum in early PD patients (Fisher et al, 2013). Such neuroplasticity in the dopaminergic signaling pathway may underlie the restoration of functional activation, as well as the reintegration of the dorsal striatum into the resting-state motor network we observed in 6-OHDA rats following NSAE (Wang et al, 2013b; Wang et al, 2014). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent PET study showed that long-term treadmill exercise partly restores the level of dopamine D2 receptor binding in the striatum in early PD patients (Fisher et al, 2013). Such neuroplasticity in the dopaminergic signaling pathway may underlie the restoration of functional activation, as well as the reintegration of the dorsal striatum into the resting-state motor network we observed in 6-OHDA rats following NSAE (Wang et al, 2013b; Wang et al, 2014). …”
Section: Discussionmentioning
confidence: 86%
“…In addition, 6-OHDA lesions resulted in a loss of FC of this region with the motor network. Four weeks of NSAE partially restored the functional activation of the dCPu during walking (Wang et al, 2013b), as well as well as resting-state functional connectivity of the dCPu with the motor network (Wang et al, 2014). Neuroplasticity in the striatum following treadmill (low-skill aerobic) exercise has been documented in naïve rodents (Ferreira et al, 2010; Real et al, 2010; Garcia et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some research results show that exercise might be helpful in retarding the progress of neurodegenerative diseases, which may be associated with the recovery of mitochondrial function by exercise. Exercise stimulates brain mitochondrial activity.…”
Section: Methods To Enhance Mitochondrial Functionmentioning
confidence: 99%
“…These differential effects of skilled versus aerobic exercise are observed at the level of anatomical specificity (circuit and brain region). Specifically, recent work by our laboratory suggests that skilled compared to non-skilled aerobic training differentially affects functional activation of the medial prefrontal cortex in parkinsonian rats during walking (54). Rats with bilateral, striatal 6-OHDA lesions were exposed to forced exercise for 4 weeks, either on a simple running wheel, considered a form of non-skilled aerobic exercise (AE), or on a complex wheel with irregularly spaced rungs, a form of skilled aerobic exercise (SAE).…”
Section: Exercise Type Blood Flow and Neurogenesismentioning
confidence: 99%